Writing a Report : How to prepare, write and present effective reports - Bowden, John, 1951- (Oxford : How To Books, 2004)
With this updated 7th edition, John Bowden offers a comprehensive and practical guide to report writing. Among the topics featured are preparation and planning, collecting and handling information, style, grammar, and writing and revising a report.
Previous ed.: 2002.
Includes bibliographical references (p. 194-195) and index.
Keywords: Business report writing; Literature